Severe acute dystonia induced by ondansetron in a paediatric patient: a case report - Kishore Nagaraju; Roshni Balachandran; Srilakshmi Ravindra Bhat; Venkatesh Karkada Srinivas; Srinivasan Ranganathan (Emergency Care Journal)
Ondansetron, a 5-HT3 serotonin receptor antagonist, is widely used to manage nausea and vomiting, particularly in postoperative recovery, chemotherapy, and paediatric gastroenteritis. Although it is well-tolerated, recent reports have raised concerns regarding dystonic reactions associated with its use, particularly in children. A 9-year-old boy (24 kg) developed acute dystonia after receiving a 2mg intravenous dose of ondansetron followed by a 4mg oral dose for symptomatic relief of acute gastroenteritis. Several hours post-administration, he exhibited abnormal muscle movement. Clinical examination showed dystonia and a positive Babinski’s sign. The patient was diagnosed with ondansetron-induced acute dystonia and was successfully treated with oral trihexyphenidyl and clonazepam. Emerging evidence indicates that ondansetron may disrupt dopaminergic-cholinergic balance in the basal ganglia, potentially triggering dystonic reactions. The Naranjo scale classified this reaction as “probable”, further supporting ondansetron as the causative agent. Although rare, dystonic reactions can occur with ondansetron, especially in paediatric populations. Clinicians should remain vigilant when prescribing ondansetron, especially in children.